2009
DOI: 10.1007/s00210-009-0470-4
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of selaginellin on glutamate-induced cytotoxicity and apoptosis in differentiated PC12 cells

Abstract: L-glutamate plays a key role in neuronal cell death associated with many neurodegenerative conditions such as cerebral ischemia, hypoxia, Alzheimer's, Huntington's, and Parkinson's diseases. Selaginellin, a component extracted from Saussurea pulvinata (Hook.et Grev.) Maximo, was assessed for its ability to protect rat pheochromocytoma (PC12) cells against oxidative toxicity induced by glutamate. The differentiated PC12 cells were pretreated with various concentrations (10(-7), 3 x 10(-7), or 10(-6) M) of selag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Klotho was found down-regulated in PC12 cells exposed to glutamate (55) and in hippocampal samples from epilepsy patients (56). Other reports suggested the important role of Klotho in the regulation of endoplasmic reticulum stress in SH-SY5Y cells (57) and in the neuroprotective effect of a plant antioxidant, ligustilide, in an AD mouse model (45).…”
Section: Discussionmentioning
confidence: 95%
“…Klotho was found down-regulated in PC12 cells exposed to glutamate (55) and in hippocampal samples from epilepsy patients (56). Other reports suggested the important role of Klotho in the regulation of endoplasmic reticulum stress in SH-SY5Y cells (57) and in the neuroprotective effect of a plant antioxidant, ligustilide, in an AD mouse model (45).…”
Section: Discussionmentioning
confidence: 95%
“…The IR spectrum revealed the presence of hydroxyl (3250 cm −1 ), conjugated carbonyl (1661, 1652 cm −1 ), aromatic (1600, 1555 and 1504 cm −1 ) groups. The UV spectrum of 1 showed absorption maxima 3 3.82 s 3.79 s 3.79 s Table 2 13 C NMR spectroscopic data for compounds 1-6 (DMSO-d 6 , 125 MHz). 3.82 (3H, s), and two meta-coupled proton signals at δ H 6.37 (1H, d, J = 2.5 Hz, H-6), 6.83 (1H, d, J = 2.5 Hz, H-8), and also exhibited the signals of the glucuronopyranosyl (GlcA) group at δ H 3.0-5.0.…”
Section: Resultsmentioning
confidence: 99%
“…1). The Fraction F was purified by semi-preparative HPLC (35% ACN-H 2 O, 3.0 ml/min, 254 nm) used to obtain compounds 5 (6.0 mg) and 6 (10.0 mg). …”
Section: Extraction and Isolationmentioning
confidence: 99%
“…PC12 cell line is derived from a pheochromocytoma of rat adrenal medulla. This cell model is also widely applied to study cellular glutamate toxicity [38]. Therefore, it is an appropriate model to investigate the protective effect of the compounds on glutamate toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…PC12 cells are more sensitive to glutamate injury; therefore, this cell model is also widely applied to study cellular glutamate toxicity [38]. Results showed that the pretreatment with C. aurantium peel and seed extracts can decrease glutamate-toxicity with different potencies.…”
mentioning
confidence: 99%